Medical and health economic assessment of radiosurgery for the treatment of brain metastasis - Müller-Riemenschneider, Falk (German Medical Science GMS Publishing House, 2009)
BACKGROUND: Radiotherapy for patients suffering from malignant neoplasms has developed greatly during the past decades. Stereotactic radiosurgery (SRS) is one important radiotherapeutic option which is defined by a single and highly focussed application of radiation during a specified time interval. One of its important indications is the treatment of brain metastases. OBJECTIVES: The objective of this HTA is to summarise the current literature concerning the treatment of brain metastasis and to compare SRS as a single or additional treatment option to alternative treatment options with regard to their medical effectiveness/efficacy, safety and cost-effectiveness as well as their ethical, social and legal implications. METHODS: A structured search and hand search of identified literature are performed from January 2002 through August 2007 to identify relevant publications published in English or German. Studies targeting patients with single or multiple brain metastases are included. The methodological quality of included studies is assessed according to quality criteria, based on the criteria of evidence based medicine. RESULTS: Of 1,495 publications 15 medical studies meet the inclusion criteria. Overall study quality is limited and with the exception of two randomized controlleed trials (RCT) and two meta-analyses only historical cohort studies are identified. Reported outcome measures are highly variable between studies. Studies with high methodological quality provide evidence, that whole-brain radiotherapy (WBRT) in addition to SRS and SRS in addition to WBRT is associated with improved local tumour control rates and neurological function. However, only in patients with single brain metastasis, RPA-class 1 (RPA = Recursive partitioning analysis) and certain primary tumour entities, this combination of SRS and WBRT is associated with superior survival compared to WBRT alone. Studies report no significant differences in adverse events between treatment groups. Methodologically less rigorous studies provide no conclusive evidence with regard to medical effectiveness and safety, comparing SRS to WBRT, neurosurgery (NS) or hypofractionated radiotherapy (HCSRT). The quality of life is not investigated in any of the studies. Within the searched databases a total of 320 economic publications are identified. Five publications are eligible for this report. The five reports have a quiet variable quality. Concerning the economic efficiency of alternative equipment, while assuming equal effectiveness, the calculations show, that economic efficiency depends to a large extend on the number of patients treated. In case the two alternative equipments are used solely for SRS, the Gamma Knife might be more cost-efficient. Otherwise an adapted linear accelerator is most likely to be beneficial because of its flexibility. One Health Technology Assessment (HTA) states, that the cost for a Gamma Knife and a dedicated linear accelerator are comparable, while an adapted version is cheaper. No reports concerning ethical, legal and social aspects are identified. DISCUSSION: Overall, quantity and quality of identified studies is limited. However, the identified studies indicate that the prognosis of patients with brain metastases is despite highly developed and modern treatment regimes still limited. Conclusive evidence with regard to the effectiveness of identified interventions is only available for the combined treatment of SRS and WBRT compared to SRS or WBRT alone. Furthermore, there is insufficient evidence to compare SRS with WBRT, NS or HCSRT. The efficiency of the different equipments depends to a great extent on the number and the indications of the patients treated. If dedicated systems are used to their full capacity, there is some evidence for superior cost-effectiveness. If more treatment flexibility is required, adapted systems seem to be advantageous. However, equal treatment effectiveness is a necessary assumption for these conclusions. The need for a treatment precision can influence the purchase decision. No reports concerning more recent therapeutic alternatives are currently available. CONCLUSION: Combination of SRS and WBRT is associated with improved local tumour control and neurological function compared to SRS or WBRT alone. However, only for patients with single metastasis there is strong evidence that this results in improved survival compared to WBRT alone. Methodologically rigorous studies are warranted to investigate SRS compared to WBRT and NS and to investigate the quality of life in patients undergoing these treatment regimes. Concerning the type of equipment used, economic efficiency depends to a great extend on the capacity at which the system can be used. Dedicated systems might be favourable for a high number of patients, while lower patient counts probably favour adapted systems with their superior treatment flexibility. Using the equipment at its full capacity may result in a limited number of machines, what in turn may give rise to the question of an equal and easy access to this technology. Studies focusing on the comparative effectiveness and cost-effectiveness of different treatment options and their combinations, especially for the German setting, are warranted.